(3ahGFO QVhjIs - (3Gdbej, eMeO SYjO GdTQja, cGf MjG aj SfI (B1099(3g`s
(3ChdgG (B:s
(3HSe Gddg(B...(3GdMeO ddg GdhGMO GdeJhMO hGdaQO GdeJaQO(B...(3hHYO aGdabjQ Edi GdZfj(B...(3eMeO GdeTJgQ HSYjO(B...(3jbhd Ef GdMceI cd GdMceI eG hQO aj GdcJGH hGdSfIs
(3BNQgG (B:s
...(3aEjGc Ke EjGc hGddg Yhfc aj OfjGc hCNQGc Cf JPjYgG(B...(3Ke Efj Ef CUHJ aef Gddg hJhajbg hCMeO Gddg hEf CNWCJ aef faSj hCSJZaQ Gddg,Gddge Ud Ydi CUai GdeUWajf hSjO Gdchfjf (B...s
(3CJe JCdjag aj (B14 (3QHjY GdChd (B1099(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B603s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B603s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdMOjK hGdeUWdMs